2011
DOI: 10.5897/ajb10.1284
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of sugar metabolism in different harvest seasons of pineapple (Ananas comosus L. (Merr.)

Abstract: In pineapple fruits, sugar accumulation plays an important role in flavor characteristics, which varies according to the stage of fruit development. Metabolic changes in the contents of fructose, sucrose and glucose and reducing sugar related to the activities of soluble acid invertase (AI), neutral invertase (NI), sucrose synathase (SS) and sucrose-phosphate synthase (SPS) were studied in winter and summer pineapple fruits in this paper. Sucrose was significantly increased in most of the harvesting winter fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Sucrose, glucose, and fructose are the major nutritional components of fleshy fruits 42 . Many studies found that sucrose, which was transported through sieve elements and then directly enters into the sink organs through the plasmodesmata or apoplastic space, is the main component for sweetness 43,44 . In accordance with the present study results, sugars in most Citrus fruits, including K .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose, glucose, and fructose are the major nutritional components of fleshy fruits 42 . Many studies found that sucrose, which was transported through sieve elements and then directly enters into the sink organs through the plasmodesmata or apoplastic space, is the main component for sweetness 43,44 . In accordance with the present study results, sugars in most Citrus fruits, including K .…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose metabolism enzyme was prepared from frozen tissues of K . tangor as described by Zhang 44 . SPS, SS-I, SS-II, AI, and NI activities were assayed using the Plant SPS, SS-I, SS-II, AI, and NI ELISA test kits (Shanghai BOYE Biology Science and Technology Co. Ltd., Shanghai, China) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of anthocyanin content followed the methodology described by Xu et al (2012). Petal samples (0.1 g) were retrieved from a -80°C freezer, ground to a powder in liquid nitrogen, and then mixed with 1 mL of methanol.…”
Section: Anthocyanin Analysismentioning
confidence: 99%
“…16 Lan et al utilized the synergistic effect between polarized electric field and photocarriers to obtain more efficient catalytic overall water splitting performance. 17 Compared with inorganic ferroelectric materials, polyvinylidene fluoride (PVDF), an organic ferroelectric material with high sensitivity of non-ultrasonic and low-frequency vibration, appears higher piezoelectric coefficient (especially the β, γ, δ phases) due to its strong polarity originated from the parallel molecular accumulation. 18 Moreover, in view of the merits of flexibility, chemical inertia, non-toxicity, etc., it is easy to be processed into fabric membrane structure through a simple polymer processing technique to obtain better operability.…”
Section: Introductionmentioning
confidence: 99%